The The influence of market orientation and product innovation on competitive advantage - Almuluk Fajar Zuhri; Perengki Susanto (Universitas Negeri Padang, 2022)
This study aimed to find out: 1) the effect of market orientation on product competitive advantage; 2) the effect of product innovation on product competitive advantage; and 3) the effect of market orientation and product innovation, simultaneously, on product. The respondents in this study were dodol kentang industry and the like, totaling 48 locations of dodol kentang industry in Kerinci regency. This study found that the variable of market orientation (X1) had a significant influence on competitive advantage in the dodol kentang small and medium industry (SMI) in Kerinci regency. This study revealed that market orientation had the significance that was eligible to be a supporting variable for competitive advantage. The correlation was positive, indicating that when market orientation carried out by the business actors was great, the competitive advantage was also high. The variable of product innovation (X2) did not significantly influence competitive advantage in dodol kentang SMI in Kerinci regency. This could be caused by the errors in filling out the questionnaires as well as the respondents’ misunderstanding when filling out the questionnaires distributed by the authors. Keywords: Market orientation, product innovation, competitive advantage